Worshiping with the church fathers - Hall, Christopher A. (IVP Academic, 2009)
Introduction -- Part I: Sacraments -- Baptism: entering the worshiping community -- Eucharist : feasting with the worshiping community -- Part II: Prayer -- The basics of prayer -- The challenge of unceasing prayer -- Further coaching on prayer -- The Lord's prayer -- Part III: Discipline -- The transforming call to the desert -- A space to draw close to God